Under the Big Dipper - Dery, Desiderius George, 1867-1942 (Salt Lake City, UT : Project Gutenberg, 2019)
"Under the Big Dipper" by Desiderius George Dery is a novel written in the early 20th century. The story introduces the complex backdrop of India, highlighting themes of ambition, despair, and the struggle against fate, as it follows a young prince facing illness and the weight of his past mistakes. The narrative opens with a focus on the deteriorating condition of a young man, who, accompanied by a concerned guardian, reflects on his choices and the shadows of a royal lineage burdened by turmoil. The beginning of the book paints a vivid picture of this young prince's life and the imminent challenges he faces as he lies sick in a small, squalid dwelling. We learn about his connections to Count Rondell, his guardian, who is deeply troubled by the prince's fate. As the Count witnesses the young man's declining health, he struggles with his own emotions, recalling the prince's past$1 (Ba life led astray by a treacherous love that ultimately derailed his prospects and led him to this tragic point. This opening segment sets a somber tone, focusing on themes of love, loss, and the heavier burdens of royalty, while foreshadowing the impending chaos in both their lives due to the political upheavals in Roumelia. (This is an automatically generated summary.)s
Release date is 2019-05-06
E-text prepared by David E. Brown and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Princesses -- Fiction; Balkan Peninsula -- Fiction; Diplomats -- Fiction